First report of bacterial leaf blight of rice caused by Sphingomonas sp. in Southern Karnataka, India - Bijoy, D; Chethana, BS; Kumar, MK Prasanna; Deepak, CA; Benherlal, PS (ORYZA-An International Journal of Rice, 2023)
Bacterial leaf blight disease is a major biotic constraint of rice cultivation distributed widely in Asia including India. During the survey (Kharif 2019) in southern Karnataka bacterial leaf blight severity ranged from 30-55% was recorded from maximum tillering onwards till the dough stage. The symptoms observed were water-soaked stripes from the tip of the leaves to white wavy margins along one or both the edges turning yellowish white and later became straw-colored and finally dries out. Symptomatic blight disease samples were collected from the field and the causal organism was isolated on nutrient agar medium following colony morphology and biochemical characteristics was studied. The isolates were isolated and tested for pathogenicity on variety Jyothi under glass house condition. DNA fingerprinting of 16SrDNA and nucleotide blast analysis of the seventeen isolates sequenced, five showed 97-100% sequence identity with Sphingomonas panni, Sphingomonas paucimobilis, and Sphingomonas sp. and rest of twelve matched to Xanthomonas oryzae and Pantoea sp.